2021
DOI: 10.5812/msnj.113501
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hope Therapy-based Training on the Happiness of Women with Breast Cancer: A Quasi-experimental Study

Abstract: Background: The prevalence of cancer and its psychological consequences has increased steadily in recent decades. Hence, parallel to providing medical interventions, psychological therapies should be provided to cancer patients. Objectives: The present study aimed to determine the effect of hope therapy-based training on the happiness of women with breast cancer. Methods: In this quasi-experimental study, 100 female patients with breast cancer admitted to the chemotherapy wards of two hospitals affiliated to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For instance, previous studies reported the effectiveness of cognitive-behavioral therapy (Bean et al, 2021), mindfulness-based stress reduction (Suh et al, 2021), progressive muscle relaxation (Ashery et al, 2021), electro acupuncture (Zhang et al, 2021), Tai Chi Chih (Irwin et al, 2017) review of the literature showed that limited interventions were done to increase the happiness of women with breast cancer. For instance, previous studies reported the efficacy of self-management (Ahmadidarrehsima et al, 2016), group positive psychotherapy (Dowlatabadi et al, 2016), hope therapy (Kondori Fard et al, 2021), and compassion-based therapy (Alighanavati et al, 2018) in increasing the happiness of women with breast cancer. The positive feature of our study in comparison with the abovementioned studies was that the technique was low cost, easy learning, availability, safety, and not time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, previous studies reported the effectiveness of cognitive-behavioral therapy (Bean et al, 2021), mindfulness-based stress reduction (Suh et al, 2021), progressive muscle relaxation (Ashery et al, 2021), electro acupuncture (Zhang et al, 2021), Tai Chi Chih (Irwin et al, 2017) review of the literature showed that limited interventions were done to increase the happiness of women with breast cancer. For instance, previous studies reported the efficacy of self-management (Ahmadidarrehsima et al, 2016), group positive psychotherapy (Dowlatabadi et al, 2016), hope therapy (Kondori Fard et al, 2021), and compassion-based therapy (Alighanavati et al, 2018) in increasing the happiness of women with breast cancer. The positive feature of our study in comparison with the abovementioned studies was that the technique was low cost, easy learning, availability, safety, and not time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies (Kondori Fard et al, 2021) with a 95% confidence interval, 90% statistical test power, and considering the probability of dropout rate, the final sample size for each group was determined to be 100 persons (200 subjects in total) using the following formula:…”
Section: Sample Sizementioning
confidence: 99%